THE ANTIBACTERIAL ACTIVITIES OF SOME PLANT DERIVED TRITERPENES - Penduka, D.; Gasa, N.P; Hlongwane, M.S; Mosa, R.A; Osunsanmi, F.O.; A.R., Opoku (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: The increase in the prevalence of multi-drug resistant bacteria has necessitated the search for new antimicrobials from alternative sources such as traditional medicinal plants. Materials and Methods: The agar well diffusion method was employed to determine the susceptibilities of four plant derived triterpenes namely, 3β-hydroxylanosta-9, 24-dien-21-oic acid (RA5), and methyl-3β-hydroxylanosta-9, 24-dien-21oate (RA3), a mixture of oleanolic acid and betulinic acid (SF1) and a mixture of 3β-acetonyloleanolic acid and 3β-acetonylbetulinic acid (SF2), at a concentration of 10 mg/ml against seven Escherichia coli, one Bacillus cereus, five Enterococcus and nine Vibrio bacteria. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined through the micro-broth dilution assay. The checkerboard method was used to determine the antibiotictriterpene interactions while the cytosolic lactate dehydrogenase test was used to determine the membrane damaging potentials of the triterpenes in comparison to 3% Triton X-100. Results: The triterpenes RA3, RA5, SF1 and SF2 had activities against 86.4%, 54.6%, 22.7% and 9.09% of the test bacteria respectively. SF1 had the lowest MIC values ranging 0.625-10 mg/ml with lower MIC values being noted against Gram negative bacteria in comparison to Gram positive bacteria; this trend was also noted among the activities of RA3 and RA5 although they had higher MIC value ranges of 1.25-10 mg/ml and 5- 10 mg/ml respectively. MBC studies proved the triterpenes to be mostly bacteriostatic. The interaction studies with ciprofloxacin were mainly ranging between indifference and antagonism. RA3 alone showed minimal membrane damaging potential with the levels of cytosolic lactate dehydrogenase released ranging from 1-36% in comparison to 3%Triton X-100 against E.coli (DSM-8695) and V. vulnificus (AL 042). Conclusion: The results hereby show the potential that the test triterpenes have as antibacterial agents, especially against the Gram negative bacteria namely E. coli and Vibrio bacteria